The Abdominal Ultrasonography Results of Cappadocia Cohort Study of Turkey Reveals High Prevalence of Fatty Liver - Sezgin, Orhan; Akpınar, Hale; Özer, Birol; Törüner, Murat; Bal, Kadir; Bor, Serhat (Turkish Journal of Gastroenterology, 2023)
Background: There is limited data about the prevalence of frequent gastrointestinal diseases in developing parts of the world based on community-based screening studies. Therefore, we aimed to present the detailed transabdominal ultrasonography results of the previously completed Turkey Cappadocia cohort study, which included a population-based evaluation of gastrointestinal symptoms and diseases in adults. Methods: This cross-sectional study was conducted in Cappadocia cohort. The transabdominal ultrasonography, anthropometric measurements, and disease questionnaires were applied to cohort persons. Results: Transabdominal ultrasonography was performed in 2797 subjects (62.3% were female and the mean age was 51 ± 15 years). Among them, 36% were overweight, 42% were obese, and 14% had diabetes mellitus. The most common pathological finding in transabdominal ultrasonography was hepatic steatosis (60.1%). The severity of hepatic steatosis was mild in 53.3%, moderate in 38.8%, and severe in 7.9%. Age, body mass index, liver size, portal vein, splenic vein diameter, hypertension, diabetes mellitus, and hyperlipidemia were significantly higher while physical activities were significantly lower in hepatic steatosis group. Ultrasonographic grade of hepatic steatosis was positively correlated with liver size, portal vein and splenic vein diameter, frequency of diabetes mellitus, hypertension, and coronary artery disease. Hepatic steatosis was observed in none of the underweight, 11.4% of the normal weights, 53.3% of the overweight, and 86.7% of the obese subjects. The percentage of hepatic steatosis cases with normal weight (lean nonalcoholic fatty liver disease) was 3.5%. The rate of lean nonalcoholic fatty liver disease in the entire cohort was 2.1%. Regression analysis revealed male gender (hazard ratio [HR]: 3.2), hypertension (HR: 1.5), and body mass index (body mass index: 25-30 HR: 9.3, body mass index >30 HR: 75.2) as independent risk factors for hepatic steatosis. The second most common ultrasonographic finding was gallbladder stone (7.6%). In the regression analysis, female gender (HR: 1.4), body mass index (body mass index: 25-30 HR: 2.1, body mass index >30 HR: 2.9), aging (30-39 age range HR: 1.5, >70 years HR: 5.8), and hypertension (HR: 1.4) were the most important risk factors for gallbladder stone. Conclusions: Cappadocia cohort study in Turkey revealed a high prevalence of hepatic steatosis (60.1%) while the prevalence of gallbladder stones was 7.6% among the participants. The results of the Cappadocia cohort located in central Anatolia, where overweight and lack of physical activity are characteristic, showed that Turkey is one of the leading countries in the world for nonalcoholic fatty liver disease. Cite this article as: Sezgin O, Akpınar H, Özer B, Törüner M, Bal K, Bor S. The abdominal ultrasonography results of Cappadocia cohort study of Turkey reveals high prevalence of fatty liver. Turk J Gastroenterol. 2023;34(6):652-664.